Morphological, pathological and molecular variability among Alternaria macrospora isolates causing leaf blight of cotton - JADHAV, B.M.; PERANE*, R.R.; KALE, A.A.; PAWAR, N.B. (Indian Phytopathology, 2011)
Variability in ten isolates of Alternaria macrospora differ with each other in respect of morphological, pathogicaland molecular basis. The average mycelial width of isolates ranged from 3.0 to 3.40 Î¼m. The size of conidia ranged from 20.81-56.23 x 9.2- 27.10 Î¼m with 1 to 6 transverse and 0 to 4 longitudinal septa. Isolates I1, I2 and I3 were found highly virulent than allother isolates. The amount of genetic variation on molecular basis was evaluated by polymerase chain reaction (PCR)amplification with a set of ten random operon primers. All the primers showed the polymorphism in the range of 64-92 per cent,however maximum polymorphism was observed by OPB-9 primer. The Jaccard similarity coefficient values among ten isolatesof A. macrospora ranged from 0.25 to 0.70. The UPGMA based dendrogram separated these isolates into two majorclusters. There was no evidence for similarity between geographical clustering and UPGMA based clustering of isolates ofA. macrospora.